Climatic and Tectonic forcing on alluvial fans in the Southern Central Andes. (15th September 2017) - Terrizzano, C.M.; García Morabito, E.; Christl, M.; Likerman, J.; Tobal, J.; Yamin, M.; Zech, R.
Abstract: Mountainous regions and their forelands commonly support a suite of landforms sensitive to climate change and tectonics. Alluvial fans in particular, are prominent geomorphological features in arid and semiarid regions which provide record for landscape, climate, and tectonic evolution. We applied 10 Be surface exposure dating on moraines and associated fan terraces of the Ansilta range (31.6°S - 69.8°W) in the Southern Central Andes with the aim of comparing both chronologies and examining the nature of alluvial fan development. The alluvial fans yield minimum ages of 19 ± 1 (T1), 120 ± 9 (T2), 185 ± 9 (T3), 389 ± 22 (T4) and 768 ± 35 (T5) ka. Minimum ages derived from moraines are 18 ± 1 (M1), 27 ± 1 (M2), 279 ± 23 (M3) and 410 ± 28 (M4) ka. M1-T1 and M4-T4 seem to be geomorphic counterparts during MIS2 and MIS11-12. Combining our glacial and alluvial database with that available from other published studies, we recognized further glacial-alluvial counterparts. The distinct phases of alluvial fan aggradation mainly correlate with moraines or have a regional extension and fall into local cold and wet times, so that climate seems to be the main forcing of alluvial fan formation at our study site, even being a region with proofed neotectonic activity. We interpret the presence of at least six cold and humid periods of alluvial aggradation which correlate with global MIS 2, 3, 5d-e, 8, 12 and 18–20. Based on these results, alluvial fans may allow landscape and climate reconstructions back to ∼750 ka in our study region. Highlights: 10 Be surface exposure dating on moraines and related fan terraces in the Central Andes are examined. The region is tectonically active and the mountain front has been suggested to be controlled by faults. Alluvial aggradation mainly correlates with moraines or have a regional extension and fall into local cold and wet periods. Climate (and not Tectonics) seems to be the main forcing of alluvial fan formation at our study site.